Nursing management of a patient with renal cell carcinoma with tumor thrombus extension into the vena cava combined with atrial fibrillation (肾癌并下腔静脉癌栓合并心房颤动1例的护理) - LI Li (黎丽) (中西医结合护理)
This paper summarized the nursing management of a patient with renal cell carcinoma with tumor thrombus extension into the vena cava combined with atrial fibrillation. Key issues of nursing included illness observation, medication guidance, skin care, prevention and nursing of lower limb vein thrombosis, nutrition support, psychological care, and so on. (总结1例肾癌并下腔静脉癌栓合并心房颤动患者的护理经验。护理要点包括病情观察、用药护理、皮肤护理、下肢静脉血栓的护理、营养支持及心理护理等。)